Agricultural credit constraints in smallholder farming in developing countries: Evidence from Nigeria. (2022) - Balana, Bedru B.; Oyeyemi, Motunrayo A.
Highlights: We examine the nature of credit constraints facing smallholder farm households using survey data and econometric models. Contrary to policy discourse and literature claim, we found that smallholders face both supply and demand-side credit constraints. Supply-side policies should focus on enhancing smallholders' capacity to possess bankable collateral, such as land titles or assets. Demand-side interventions need to focus on farmers' risk perception, information access, transaction costs and capacity strengthening. Abstract: The agricultural sector in developing countries like Nigeria is characterized by low productivity, driven partly by low use of modern agricultural technologies. Poor access to credit is seen as a key barrier to adoption of these technologies. Policy discourses and literature often associate credit constraints by smallholders with supply-side factors such as inadequate access to sources of rural finance or high costs of borrowing. However, demand-side factors, such as smallholders' risk-averse behavior, high transaction costs and information asymmetry predominate in rural areas of developing countries equally play important roles in the functioning of rural credit market. Using a nationally representative LSMS-ISA data from 5000 smallholders in Nigeria and seemingly unrelated econometric models, we examine the nature of rural credit, the factors affecting rural credit, and the effects of credit constraints on adoption of four agricultural technologies – inorganic fertilizer, improved seed, agrochemicals, and mechanization. Contrary to policy discourses focusing on supply-side factors of rural credit, we found that demand-side factors are equally important for improving access and utilization of rural credit. On the supply side, inadequate collateral is the key constraint; hence supply-side policies should focus on enhancing smallholders' capacity to possess bankable collateral, such as land title or assets. On the demand-side, interventions such as crop insurance, information access and extension services are needed to increase credit access, technology adoption, and smallholder's agricultural productivity.